Mechanisms of action of cytoplasmic microRNAs. Part 2. MicroRNA-mediated post-translational silencing - A.E. Abaturov; V.L. Babуch (Zaslavsky O.Yu., 2022)
The scientific review presents the mechanisms of action of cytoplasmic miRNAs, namely miRNA-mediated posttranslational silencing. To write the article, information was searched using Scopus, Web of Science, MedLine, PubMed, Google Scholar, EMBASE, Global Health, The Cochrane Library, CyberLeninka databases. It is stated that protein synthesis is a complex process which involved many regulators. It is known that the translation process consists of three main stages: initiation, elongation of the polypeptide chain and termination. It is presented that dozens of "basic" factors and numerous accessory proteins, both regulators and repressors of the process, take part in the translation initiation. The authors provide a kinetic model proposed by Christopher S. Fraser. According to this model, translation initiation is a ranked process. It is emphasized that subsequently the ribosome interacts with the beginning of the coding nucleotide sequence of mRNA. Modifications of nucleotides by elongation factors in the anticodon of tRNA regulate the dynamics of ribosome function and, thus, fine-tune the rate of protein synthesis. The authors state that translation termination is induced by the interaction of the decoding A-region of the ribosome with one of the three stop codons (UAA, UAG or UGA) of mRNA. "Termination factors" are also involved in the termination of translation. Scientists say that the main factors that regulate the functional activity of mRNA act on the cap and poly(A)tail, which protects mRNA from exonuclease action. Thus, various proteins surround mRNA molecule in the cell and support the existence and functional activity of mRNA. Each mRNA region interacts with a specific spectrum of RNA-binding proteins. The initiation of translation is a ranked process and is inextricably linked with mRNA degradation. It is widely believed that translation is largely controlled during the initiation period. The mechanism of silencing caused by mRNA degradation depends on the size of the complementary region.